2017
DOI: 10.1177/1099636217733369
|View full text |Cite
|
Sign up to set email alerts
|

The role of a composite polycarbonate-aerogel face shield in protecting the human brain from blast-induced injury: A fluid–structure interaction (FSI) study

Abstract: Background Blast-induced traumatic brain injury is the most prevalent injury sustained by combat soldiers at the frontline. The current study aims to investigate the effectiveness of composite polycarbonate-aerogel face shields with different configurations in mitigating blast-induced brain injuries. Method A series of dynamic fluid–structure interaction simulations of a helmeted head subjected to a frontal free field blast was performed, to evaluate the effectiveness of the current conventional polycarbonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Goggles act similar to a face shield or a visor. Several studies 31,33,36,39,43 have shown the excellent ability of face shields in mitigating the ICP. For example, Tse et al 43 studied the protective performance of single-layered and multi-layered face shields for frontal blast exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goggles act similar to a face shield or a visor. Several studies 31,33,36,39,43 have shown the excellent ability of face shields in mitigating the ICP. For example, Tse et al 43 studied the protective performance of single-layered and multi-layered face shields for frontal blast exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies 31,33,36,39,43 have shown the excellent ability of face shields in mitigating the ICP. For example, Tse et al 43 studied the protective performance of single-layered and multi-layered face shields for frontal blast exposure. They showed that the multilayered face shield provides a better blast wave attenuation performance, as it benefits from the polycarbonate exterior shell for structural integrity and inner aerogel filler for blast wave mitigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-strength and high-modulus polymer composites are produced by reinforcing the polymer matrix with high-strength and high-modulus fibers, the reinforcing fibers are employed to increase the strength and stiffness of the material, and the load is transferred to the fibers via the viscoelastic displacement of the matrix under stress [74]. The reinforcing fibers that are commonly used for enhancing performance are glass fiber (GF) [20,39,[70][71][72][73]75], basalt fiber (BF) [22,23,76,77] and carbon fiber (CF) [78][79][80][81]. GF are of two types: chopped glass fiber and milled glass fiber (MG), of which MG is mostly used as reinforcing and filling media in plastic composites, adhesives and coatings.…”
Section: Incorporation Of Reinforcing Materialsmentioning
confidence: 99%
“…Tse et al [16] analyzed numerically the performance of face shields of a polycarbonate-aerogel composite with ACH helmet subjected to different blast loadings. The use of aerogel showed better protection capability than the classical polycarbonate face shields.…”
Section: Introductionmentioning
confidence: 99%